Innovating a system for producing and distributing hybrid oil palm seedlings to smallholder farmers in Benin - VISSOH, VINASSÉHO PIERRE; TOSSOU, COCOU RIGOBERT; AKPO, Essegbemon; KOSSOU, KODJO DANSOU; JIGGINS, Janice (My University, 2017)
This article analyses the development of a system for producing and distributing hybrid oil palm seedlings to small-scale famers. The existing seed system had become so corrupted that the seedlings actually planted were largely of unimproved kinds. The article describes institutional experiments carried out by two Innovation Platforms (IPs) in order to improve the oil palm seed system. Theory Guided Process Inquiry was used to document, evaluate and analyse these interventions. The experiments catalysed changes in interpersonal and inter-organisational power relationships that enabled further co-learning and co-construction of understanding and action among key stakeholders in the oil palm domain. The IPs and those who became local champions of seed system innovation, also triggered change in institutional behaviours, technologies, and practices that further improved the integrity of the seed system. Official nursery holders must now be trained, registered and licensed by local government. Farmers are encouraged to source hybrid seedlings only from licensed nurseries. These achievements were then shared and discussed with officials and higher level government leaders, drawing on IP members’ pre-existing professional and personal networks. Improvement of the oil palm seed system was included in the government’s latest 5-year development plan.
Keywords: institutional development / stakeholders / innovation / seedling system / oil palm / Benin; renforcement institutionnel / innovation / exploitation agricole / système semencier / palmier à huile / Bénin